2015
DOI: 10.1111/caim.12133
|View full text |Cite
|
Sign up to set email alerts
|

Technological Environment and Technology Entrepreneurship: A Cross‐Country Analysis

Abstract: Recent years have seen growing interest in the influence of the environment on entrepreneurship. However, little is known about the impact of the country‐level technological environment on the creation of new technology‐based firms. This study investigates the relationship between the technological environment (measured by the amount of investment in R&D, and access to information and communication technology [ICT] infrastructure) and technology entrepreneurship, in 54 countries during the years 2005 to 2010. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 78 publications
0
26
0
14
Order By: Relevance
“…Researchers found that the significant investments in research and development, strong technological environments and robust economic standards of innovation-driven economies enabled them to create entrepreneurs with high impact (Colovic & Lamotte 2015). As a result, they enjoy an abundance of high-impact technological entrepreneurs to a greater extent than economies dominated by necessity entrepreneurs.…”
Section: Entrepreneurship and Economic Developmentmentioning
confidence: 99%
“…Researchers found that the significant investments in research and development, strong technological environments and robust economic standards of innovation-driven economies enabled them to create entrepreneurs with high impact (Colovic & Lamotte 2015). As a result, they enjoy an abundance of high-impact technological entrepreneurs to a greater extent than economies dominated by necessity entrepreneurs.…”
Section: Entrepreneurship and Economic Developmentmentioning
confidence: 99%
“…O setor de tecnologia é onde o empreendedorismo tecnológico (TE) tem maior probabilidade de ocorrência pela sensibilidade dos atores no setor de Tecnologia da Informação, onde as velozes mudanças tecnológicas e ao valor de mercado, pois as TICs promovem a criação de novos empreendimentos, mudando radicalmente o relacionamento entre empreendedorismo e inovação (Colovic & Lamotte, 2015).…”
Section: Empreendedorismo Tecnológicounclassified
“…Assim como a produção acadêmica, o desenvolvimento de empresas baseadas em tecnologia tem certa concentração em consequência do acesso à infraestrutura de TIC e o investimento em pesquisa e desenvolvimento (P&D) que influencia a probabilidade de TE regional e ameniza a imitabilidade dos recursos e das inovações (Colovic & Lamotte, 2015;Venkataraman, 2004). Desta forma, o contexto ambiental no qual a atividade empreendedora é manifesta deve ser analisado cuidadosamente na formulação de explicações sobre o TE (Shane & Venkataraman, 2003).…”
Section: Empreendedorismo Tecnológicounclassified
See 2 more Smart Citations